2018
DOI: 10.1177/0706743718787795
|View full text |Cite
|
Sign up to set email alerts
|

“I Can’t Crack the Code”: What Suicide Notes Teach Us about Experiences with Mental Illness and Mental Health Care

Abstract: This study highlights unique perspectives by suicide decedents, whose voices and experiences may not have been heard otherwise, addressing a critical deficit in existing literature. These insights can potentially enrich clinical care or strengthen existing suicide prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…As such, the findings cannot be generalised to a larger population or to other suicide methods. However, the sample size was comparable to other indepth studies of suicide notes (Cheung, Merry, & Sundram, 2015;Furqan, Sinyor, Schaffer, Kurdyak, & Zaheer, 2019).…”
Section: Limitations and Future Directionssupporting
confidence: 61%
“…As such, the findings cannot be generalised to a larger population or to other suicide methods. However, the sample size was comparable to other indepth studies of suicide notes (Cheung, Merry, & Sundram, 2015;Furqan, Sinyor, Schaffer, Kurdyak, & Zaheer, 2019).…”
Section: Limitations and Future Directionssupporting
confidence: 61%
“…The study also found that high-income countries are significantly more likely to have child and adolescent mental health strategies, dedicated mental health authority and suicide prevention programs, relative to LMIC. More importantly, given the robust link between mental health problems and tendency for suicide particularly in the high-income countries [ 9 , 11 ], it is plausible to reason that programs and initiatives designed to promote and restore mental health functioning will contribute to a reduction in suicide rate. In contrast, however, the study found that macro-level mental health indicators examined in this study (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We used ten composite quotes to share example predictions of our system on text that could be predictive/indicative of self-harming and/or suicidality. These composite quotes were created by Furqan et al [22] , and were derived from qualitative research that synthesized primary themes noted in a selection of suicide notes that made explicit mentions of mental illness and/or mental healthcare. To assess the role of individual words (or tokens) in the classification of the quote, we iteratively perturbed each token and replaced it with an unknown token outside of the model's vocabulary and re-ran the prediction.…”
Section: Composite Quotesmentioning
confidence: 99%